INCREASE JOBS FOR TRANSPORT COMPANIES IN UZBEKISTAN BY INCREASING THE PURCHASE OF PRODUCTS MANUFACTURED BY PEOPLE WITH DISABILITIES (American Journal of Business Management, Economics and Banking, 2023)
In this article, specialized enterprises for people with disabilities in the republic are studied. Issues such as the condition of the enterprises, the extent to which the available opportunities are being used, the purchasing power of the manufactured products, the created conditions were analyzed in depth, and proposals were prepared for the promotion of transport enterprises by purchasing the products produced in these enterprises.